One-piece flow vs. batching : a guide to understanding how continuous flow maximizes productivity and customer value /: a guide to understanding how continuous flow maximizes productivity and customer value. (2015) - Protzman, Charles; McNamara, Joe; Protzman, Dan
No abstract available